# -2(18r+10)+18r=-18r-20

## Simple and best practice solution for -2(18r+10)+18r=-18r-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -2(18r+10)+18r=-18r-20 equation:

Simplifying
-2(18r + 10) + 18r = -18r + -20

Reorder the terms:
-2(10 + 18r) + 18r = -18r + -20
(10 * -2 + 18r * -2) + 18r = -18r + -20
(-20 + -36r) + 18r = -18r + -20

Combine like terms: -36r + 18r = -18r
-20 + -18r = -18r + -20

Reorder the terms:
-20 + -18r = -20 + -18r

Add '20' to each side of the equation.
-20 + 20 + -18r = -20 + 20 + -18r

Combine like terms: -20 + 20 = 0
0 + -18r = -20 + 20 + -18r
-18r = -20 + 20 + -18r

Combine like terms: -20 + 20 = 0
-18r = 0 + -18r
-18r = -18r

Add '18r' to each side of the equation.
-18r + 18r = -18r + 18r

Combine like terms: -18r + 18r = 0
0 = -18r + 18r

Combine like terms: -18r + 18r = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.`